Secondary Metastatic Gastric Melanoma - Chowdhury, Abdullah Al Mamun; Khan, Meshkat Uddin; Hussain, Md Margub (Journal of Bangladesh College of Physicians and Surgeons, 2020)
Gastrointestinal melanomas are commonly metastatic from a cutaneous origin. They cause significant cancer related mortality. A 47- year - old male patient presented with severe pallor and prostration due to profuse upper GI bleeding. He was urgently managed with fluid and blood transfusion. Endoscopy revealed gastric mass and CT showed gastric neoplasm with abdominal lymphadenopathy but endoscopic biopsy revealed inflammatory lesion. He had history of malignant melanoma of right third toe three years back which was managed with surgery and chemotherapy. Exploratory laparotomy was done and biopsy was taken from gastric lesion as well as enlarged lymph nodes. Histopathology revealed melanoma from both specimens. Prognosis is bad. Counseling and collaboration with different relevant disciplines are essential. Management is directed to symptom relieve as well as lengthening survival. J Bangladesh Coll Phys Surg 2021; 39(1): 68-75